IICA's Caribbean strategy and current initiatives in the Caribbean region - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2021)
This document explain the MTP has the following basic principles: decentralization with five centres including the Caribbean with the largest number of countries, participatory approach (outside and within IICA), market or client led, flexibility, and development of strategic alliances. (MV) Este documento explica que el PMP tiene los siguientes principios básicos: descentralización con cinco centros incluyendo el Caribe con mayor número de países, enfoque participativo (fuera y dentro del IICA), mercado o liderado por clientes, flexibilidad y desarrollo de alianzas estratégicas. (MV)